A proposed conception of the role of educational media in light of the challenges of the age "Analytical study" - Dr. Anas Odibat; Dr. Heba Tawfiqe Odah Abu Eyadah (International Journal on Integrated Education, 2023)
The current study aims to identify the role of educational media in consolidating principles, values ​​and societal security in light of the changing challenges of the era, to get out of them with a proposed vision that supports sound educational media and enhances peace, security and tranquility and rejects all forms of violence, hatred, extremism and fanaticism in creative and innovative ways and achieves the hope of broadcasting positive messages through the means Digital media that contribute to improvement, development, change, solving current problems and crises, supporting scientific research and investing it in rational decision-making, by analyzing and reviewing previous research and studies and educational literature that dealt with educational media and its role in facing current crises and challenges in a way that ensures an integrated therapeutic vision to confront contemporary challenges. The current study will differ from previous studies in the methodology of the study, as the current study depends on the analysis of educational literature through the descriptive analytical and developmental approach and in light of the results of previous studies. The study provides a set of recommendations.